Transcriptional re-programming of liver-resident iNKT cells into T-regulatory type-1-like liver iNKT cells involves extensive gene de-methylation - Montaño, Javier; Garnica, Josep; Yamanouchi, Jun; Moro, Joel; Solé, Patricia; Mondal, Debajyoti; Serra, Pau; Yang, Yang; Santamaria, Pere (Frontiers in Immunology, 2024)
Unlike conventional CD4+ T cells, which are phenotypically and functionally plastic, invariant NKT (iNKT) cells generally exist in a terminally differentiated state. Naïve CD4+ T cells can acquire alternative epigenetic states in response to different cues, but it remains unclear whether peripheral iNKT cells are epigenetically stable or malleable. Repetitive encounters of liver-resident iNKT cells (LiNKTs) with galactosylceramide (aGalCer)/CD1d-coated nanoparticles (NPs) can trigger their differentiation into a LiNKT cell subset (LiNKTR1) expressing a T regulatory type 1 (TR1)-like transcriptional signature. Here we dissect the epigenetic underpinnings of the LiNKT-LiNKTR1 conversion as compared to those underlying the peptide-major histocompatibility complex (pMHC)-NP-induced T-follicular helper (TFH)-to-TR1 transdifferentiation process. We show that gene upregulation during the LINKT-to-LiNKTR1 cell conversion is associated with demethylation of gene bodies, inter-genic regions, promoters and distal gene regulatory elements, in the absence of major changes in chromatin exposure or deposition of expression-promoting histone marks. In contrast, the naïve CD4+ T cell-to-TFH differentiation process involves extensive remodeling of the chromatin and the acquisition of a broad repertoire of epigenetic modifications that are then largely inherited by TFH cell-derived TR1 cell progeny. These observations indicate that LiNKT cells are epigenetically malleable and particularly susceptible to gene de-methylation.